Government Monopoly vs. Private Competition - Howes, Osborne (Quarterly Journal of Economics, 1888)
Journal Article Government Monopoly vs. Private Competition Get access Osborne Howes, Jr. Osborne Howes, Jr. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 2, Issue 3, April 1888, Pages 353–361, https://doi.org/10.2307/1879419 Published: 01 April 1888